Teachers' technology adoption and practices: lessons learned from the IWB phenomenon. Issue 4 (8th August 2018) - Kearney, Matthew; Schuck, Sandy; Aubusson, Peter; Burke, Paul F.
Abstract: The twenty-first century has seen unprecedented investment from governments around the world in educational technologies in schools. This paper investigates Australian teachers' adoption and use of a popular technology that has been extensively supported by governments and school systems: the interactive whiteboard (IWB). The study suggests that a number of the barriers identified in the early days of adoption and use of this technology, such as professional support and access, still remain for many teachers, thereby impeding effective practices. The research also found that primary school teachers were using the technology in diverse ways, in contrast to secondary teachers who were using the IWB mainly for instructionist, presentational purposes. We conclude by considering various ways of reducing the effect of the identified barriers to support implementation of educational technologies in the classroom, especially the next generation of technologies promoted by governments and systems.